HALAL FASHION: PELUANG EKONOMI DARI INDUSTRI MODEST FESYEN INDONESIA - Zaki, Khozin; Nazir, Ahmad (Universitas Mathla’ul Anwar Banten, 2025)
Data from The State of the Global Islamic Economy Report 2023/2024 published by Dinar Standard shows that Indonesia has risen to third place in the Global Islamic Economic Indicator (GIEI) ranking, below Malaysia and Saudi Arabia. Specifically in the Halal Fashion aspect, Indonesia is included in the top three modest fashion industries in the world, alongside the United Arab Emirates and Turkey. This study attempts to explore opportunities that are projected to arise from efforts to develop halal fashion using a descriptive analysis approach through literature review. With a large domestic market potential and rapid growth of the Muslim fashion industry, Indonesia continues to strengthen its position as the center of the global modest fashion trend. The results of the study see that based on World Population Review data, the number of Muslims in the country in 2025 will reach more than 229 million people or more than 87% of the total population of 285.7 million people. This is a great opportunity for Indonesia to become the center of world fashion because the Indonesian fashion industry is competitive in the global market. This opportunity requires improvements in various aspects of the quality of raw materials, technology, human resources, markets, capital and community consumption itself for Muslim fashion and also government support for designers and the fashion world so that Indonesia can become a center for modest halal fashion.